Sharing Economy and the Quality of Young Adults’ Life as Seen by Members of Internet Groups - Anna Irena SZYMAŃSKA (Communications of International Proceedings, 2021)
The main objective of the article was to demonstrate and prove the role of the sharing economy (SE) in improving the quality of life of young adults. Four theses were formulated during the research. Subsequently, there were confirmed by empirical research. Focus Group Interviews (FGI) was the research method applied. 72 persons in total took part in the research, including members of Social Economy (SE) related Internet groups. The research will be continued in the MINIATURA 4 project financed by the National Centre of Science (No. DEC-2020/04/X/HS4/00515). During the research, it was observed that the SE may contribute to improving the community’s living conditions (having) (e.g. access to luxurious goods). It also affects interpersonal relations, social trust (loving), personal development and self-fulfilment (being). Also, the SE has a positive impact on the environment, therefore it is aligned with environmental goals and sustainable consumptions.
Keywords: Focus group interview; sharing economy; quality of life; young adults.